Estimating respiratory frequency from autoregressive spectral analysis of heart period. - Thayer, J.F (IEEE Engineering in medicine and biology magazine)
In this article we report the results of a pilot study and a larger investigation that examined the relationship between respiration frequency assessed using the traditional mercury strain gauge and using the central frequency of the HF component derived from autoregressive spectral analysis.